2009
DOI: 10.1016/j.rmed.2008.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Improving mucociliary clearance in chronic obstructive pulmonary disease

Abstract: Patients with COPD usually experience mucus hypersecretion as a result of airway inflammation and response to noxious stimuli. These in turn lead to worsening airway resistance, impaired airflow, increased work of breathing, dyspnoea and exercise intolerance. Mucus hypersecretion may also lead to increased exacerbations and poor health related quality of life (HRQL). Institution based pulmonary rehabilitation programs incorporating airway clearance techniques have been shown to improve HRQL, reduce dyspnoea an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 59 publications
0
49
0
9
Order By: Relevance
“…The total CAT score was calculated by summing the points of each variable, the higher scores represent worse health. [8][9][10][11][12] It was classified into four categorizes; low (< 10), medium (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), high (21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and very high (> 30). (FEV1% pred = predicted amount as a percentage of the forced expiratory lung volume in one second; 6MWD = six minute walking distance; MMRC = modified medical research council dyspnea scale; BMI = body mass index.…”
Section: Copd Assessment Test (Cat)mentioning
confidence: 99%
See 1 more Smart Citation
“…The total CAT score was calculated by summing the points of each variable, the higher scores represent worse health. [8][9][10][11][12] It was classified into four categorizes; low (< 10), medium (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), high (21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and very high (> 30). (FEV1% pred = predicted amount as a percentage of the forced expiratory lung volume in one second; 6MWD = six minute walking distance; MMRC = modified medical research council dyspnea scale; BMI = body mass index.…”
Section: Copd Assessment Test (Cat)mentioning
confidence: 99%
“…During expiration through the Flutter, the expiratory flow move the steel ball up and down, creating PEP and oscillations with a back transmission to the patient, to facilitate mucus expectoration. 24,25 The patients placed in erect positions; in a well-supported chair with a neutral lumbar spine to enhances the function of the diaphragm and the pelvic floor, minimizes musculoskeletal stress and to ensure the best transmission of vibration to chest wall. 26 They were instructed to inhale deeply and hold his/her breathe for 2-3 second, then expire slowly through the Flutter valve, which cause oscillations of the steel ball inside the cone of the Flutter.…”
Section: • the Flutter Mucus Clearance Devicementioning
confidence: 99%
“…The STT of smokers with COPD (16.5 [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] [6 -16] min) (P Ͻ .001). There was no difference in STT values between smokers with COPD and current smokers, and these values in ex-smokers with COPD were similar to those for the control group (Fig.…”
Section: Saccharin Transit Time Datamentioning
confidence: 99%
“…12 Studies have shown that the impairment of MCC in smokers was related to the intensity of the smoking habit 13 and that smoking cessation improved nasal MCC by 15 d after quitting smoking and that the improvement persisted over 6 months. 14 Some studies found modified mucociliary function in subjects with COPD, 15,16 and ciliary beat frequency was markedly lower in these subjects. 17 It is known that smoking cessation reduces the decline in FEV 1 , respiratory symptoms, and airway inflammation and that it improves longterm prognosis.…”
Section: Introductionmentioning
confidence: 97%
“…EPOC se caracteriza por obstrucción crónica del flujo espiratorio manifestada clínicamente como bronquitis crónica con o sin enfisema, fibrosis, daño de tejido e inflamación de la vía aérea pequeña 39 . Su principal causa es el tabaquismo 40 .…”
Section: Enfermedad Pulmonar Obstructiva Crónica (Epoc)unclassified